Effect of Rotation on the Piezoelectric Wave Impedance Characteristics - YUAN, Xiaoguang; HAO, Chaoyu; JIANG, Quan (Archives of Acoustics, 2023)
The dependence of piezoelectric wave impedance on the rotation speed is investigated theoretically and numerically. The Coriolis force due to rotation is introduced into the piezoelectric motion equations, which is solved by the harmonic plane wave solution. It is shown that the wave impedance variations of longitudinal and transverse waves due to rotation are clearly different. The longitudinal wave impedance continuously increases with a small rotation ratio and one transverse wave impedance is almost irrespective of a rotation ratio. In contrast, the rotation applies a big impact on the other transversal wave impedances in the piezoelectric crystal which decreases monotonically with the rotation speed. Such characteristics are significant in piezoelectric transducers and sensors.